Intestinal parasitic infection: prevalence, knowledge, attitude, and practices among schoolchildren in an urban area of Taiz city, Yemen - Talal Alharazi; Omar AA Bamaga; Nazeh Al-Abd; Jerold C Alcantara (AIMS Press, 2020)
Background Intestinal parasitic infections (IPIs) are regarded as one of the main public health problems and socio-economic issues adversely affecting the health of millions of people worldwide. Our study aimed to describe the knowledge, attitude, and practices of local urban schoolchildren in Taiz City towards intestinal parasitic infections. Methods and material This is a cross-sectional study conducted in Taiz, Yemen from March to May 2019. A total of 385 schoolchildren were selected using a random sampling technique from 7 primary schools. Wet-mount microscopic examination, formol-ether concentration techniques, and Lugols' iodine were employed in parasite detection and cyst identification. Results Of the 385 schoolchildren examined for IPIs, 107 (27.8%) were positive for the presence of enteric parasites, some having multiple infections. The prevalence was slightly higher in males 46 (28.6%) than in females 61 (27.2%) but have no statistical difference (P = 0.77). Entamoeba histolytica/dispar was the most common infection with 16.4% of cases. A substantial percentage (40.5%) of the respondents displayed poor knowledge. The respondents also revealed inappropriate attitudes and practices that contribute to the prevalence of IPIs in the study. Conclusions The study revealed the prevalence of intestinal parasites among the schoolchildren in Taiz, Yemen, suggesting that IPIs remain a major public health problem. Entamoeba histolytica/dispar was the most prevalent intestinal parasites identified among the schoolchildren. Age, poor knowledge of the mode of transmission, prevention, and acquisition of IPIs, and poor habitual hygiene practices increase the risk of acquiring intestinal infections.